Comprehensive geriatric assessment in newly diagnosed older myeloma patients: a multicentre, prospective, non-interventional study. (18th October 2021) - Yao, Yuan; Sui, Wei-Wei; Liao, Ai-Jun; Wang, Wei; Chen, Li-Juan; Chu, Xiao-Xia; Bao, Li; Cen, Xi-Nan; Fu, Rong; Liu, Hui; Sun, Chun-Yan; Jin, Feng-Yan; et al.
Abstract: Background: Multiple myeloma is a disease of the older people, whose prognoses are highly heterogeneous. The International Myeloma Working Group (IMWG) proposed a geriatric assessment (GA) based on age, functional status and comorbidities to discriminate between fit and frail patients. Given the multidimensional nature of frailty and the relatively recent exploration of frailty in the field of MM, reaching a consensus on the measurement of frailty in MM patients remains challenging. Objective: We sought to assess the feasibility of performing a comprehensive GA (CGA) in older MM patients in a real-world and multicentre setting and to evaluate their baseline CGA profiles. Results: We studied 349 older patients with newly diagnosed MM (age range, 65–86 years). Our results showed that a CGA is feasible for older MM patients. Using the IMWG-GA criteria, we identified significantly more frail patients in our cohort comparing to in the IMWG cohort (43% vs 30%, P = 0.002). In the IMWG-GA 'fit' group, risk of malnutrition, depression and cognitive impairment remains. The median follow-up time was 26 months (range 1–38). The median overall survival (OS) was 34.7 months, and the estimated 3-year OS rate was 50%. A high MNA-SF score (MNA-SF ≥ 12), low GDS score (GDS ≤ 5) and high CCI score (CCI ≥ 2) can be used to predict the OS of older patients with newly diagnosed MM. This study is registered at www.clinicaltrials.gov (NCT03122327). Conclusions: Our study justifies the need for a CGA in older patients with newly diagnosed MM.